RESPON PEMBERIAN KOMPOS CAMPURAN DAN POC HAYATI TERHADAP PRODUKTIVITAS TANAMAN BAWANG MERAH - Budianto, Rhiki; Ardina, Ardina (Agriculture, 2025)
Onions are a type of horticultural commodity that is essential for seasoning food. The ever-increasing demand for red onion production has led a continuous increase in red onion production in the field to meet market needs. Shallot productivity can be increased through fertilization. The fertilization that can be done and is considered safe is organic fertilizer. Therefore, this study aims to determine the effect of mixed compost and biological POC on onion plants. This research was conducted in Sendang Rejo Village, Binjai, from November to February 2020, using a Randomized Block Design with 2 factors. The forst factor is a mixture of goat maure compost and rice straw (control, 1, 2, and 3 kg/plot), and the second factor is biological POC (control, 300, 400, 500 ml/liter water/plot). This research results show that the application of mixed compost and biological POC significantly affects plant height parameters at 3, 4, and 5 weeks after planting. The interaction between the two fators did not significantly affect all observed parameters.